Energy transition scenarios: What policies, societal attitudes, and technology developments will realize the EU Green Deal?. (15th January 2022) - Hainsch, Karlo; Löffler, Konstantin; Burandt, Thorsten; Auer, Hans; Crespo del Granado, Pedro; Pisciella, Paolo; Zwickl-Bernhard, Sebastian
Abstract: The European Green Deal has been heralded as the "Europe's man on the moon moment" as it aims to achieve 100% GHG reductions by 2050. Achieving the decarbonization of the energy system will be driven by a combination of factors and synergies between technological development, policy exertion and societal attitudes. In this paper, we present an original set of future storylines until the year 2050 to inspire modelers, policy makers, industry actors, and the public to understand: Without technological developments in the next decades, to what extent can we rely on societal commitment or stronger cooperation within the EU to achieve climate targets? What technological innovations could become a cornerstone of an effective European energy transition? Through analyzing four pathways (shaped by the crossroads of policy-technology-society developments), results indicate that high electrification rates are imminent to achieve a rapid decarbonization. This implies that technology development and deployment must go hand-in-hand with strong policy enforcement in the short-term to speed-up the energy transition. Then, based on a review of European energy transition scenarios, these and other insights are compared vis-à-vis with other scenarios studies to identify similarities of pathway results and to elaborate on consolidated findings relevant to the EU Green Deal. Highlights: Analyses of rising number of 100% renewable energy scenarios requires extensive knowledge about the tools and methodology. A novel 3-dimensional scenario process is used to generate and evaluate four different energy transition pathways. Comparison of seven different 100% scenarios highlights common no-regret options for the European energy transition. The EGD includes many of these no-regret options but still lacks in ambition when it comes to the speed of the transition.